Advanced three-dimensionally engineered simulation model for aortic valve and proximal aorta procedures. (14th April 2020) - Russo, Marco; Koenigshofer, Markus; Stoiber, Martin; Werner, Paul; Gross, Christoph; Kocher, Alfred; Laufer, Guenther; Moscato, Francesco; Andreas, Martin
Abstract: OBJECTIVES: A 3-dimensionally (3D) engineered model for simulation of aortic valve and proximal aortic procedures is a reliable tool both for training young surgeons and for simulating complex cases. To achieve a realistic simulation, the artificial model should reproduce the angles and orientations of the cardiac structures based on the patient's anatomical condition, reproduce tissue mechanical characteristics and be easy to obtain and easy to use. The goal of the study was the production and validation of realistic training models, based on the patient's actual anatomical characteristics, to provide training for aortic valve procedures. METHODS: An anatomical model was manufactured using 3D printing and silicone casting. The digital anatomical model was obtained by segmenting computed tomography imaging. The segmented geometrical images were processed and a casting mould was designed. The mould was manufactured on a 3D printer. Silicone was cast into the mould; after curing, the finished model was ready. The realistic reproduction was evaluated by mechanical hardness tests and a survey by cardiac surgeons. RESULTS: Six 3D silicone models were produced that represented the patient's anatomy including aortic valve leaflets, aortic root with coronary ostia, ascending aorta and proximal arch. Aortic valve replacement was performed, and 100% of the participants evaluated the model in a survey as perfectly reproducing anatomy and surgical handling. CONCLUSIONS: We produced a realistic, cost-effective simulator for training purposes and for simulation of complex surgical cases. The model reproduced the real angulation and orientation of the aortic structures inside the mediastinum, permitting a real-life simulation of the desired procedure. This model offers opportunities to simulate various surgical procedures.